Characterization of gas-expanded liquid-deposited gold nanoparticle films on substrates of varying surface energy - Hurst, Kendall M (Langmuir : the ACS journal of surfaces and colloids, 2011)
Dodecanethiol-stabilized gold nanoparticles (AuNPs) were deposited via a gas-expanded liquid (GXL) technique utilizing CO(2)-expanded hexane onto substrates of different surface energy. The different surface energies were achieved by coating silicon (100) substrates with various organic self-assembled monolayers (SAMs). Following the deposition of AuNP films, the films were characterized to determine the effect of substrate surface energy on nanoparticle film deposition and growth. Interestingly, the critical surface tension of a given substrate does not directly describe nanoparticle film morphology. However, the results in this study indicate a shift between layer-by-layer and island film growth based on the critical surface tension of the capping ligand. Additionally, the fraction of surface area covered by the AuNP film decreases as the oleophobic nature of the surfaces increases. On the basis of this information, the potential exists to engineer nanoparticle films with desired morphologies and characteristics